Comparison of Efficacy and Safety of Different Guided Technologies Combined With Ultrathin Bronchoscopic Biopsy for Peripheral Pulmonary Lesions - Zhihan Zhang; Junbao Zhang; Xi Chen; Junfeng Yan; Cao Zeng; Ping Xu (The Clinical Respiratory Journal)
ABSTRACT Introduction Various bronchoscopic guidance techniques have emerged to improve the diagnostic yield of peripheral pulmonary lesions (PPLs), especially when combined with ultra‐thin bronchoscopy. However, uncertainties exists in the convenience, accuracy rate, and complications of these techniques. We compared the feasibility, accuracy rate, and complication rates of transbronchial biopsy of PPLs sampled by the standard thin‐layer CT navigation combined with ultrathin bronchoscopy (CTNUTB), the Lungpro virtual navigation combined with ultrathin bronchoscopy (VNUTB), and electromagnetic navigation combined with ultrathin bronchoscopy (ENUTB). Methods Retrospectively identified were 256 patients sampled with transbronchial biopsy of PPLs. Eligible patients referred for CTNUTB, VNUTB, and ENUTB from January 2017 to December 2021 were included. We comprehensively compared the accuracy rate, feasibility, and complication rates for each method. Results There was no significant difference in the accuracy rate of CTNUTB, VNUTB, and ENUTB (p = 0.293). The operation time via Lungpro navigation was the shortest (14.4 min, p < 0.001). The planning time via CT planning was the shortest (7.36 min, p < 0.001). There was no difference in the incidence of complications such as hemorrhage, pneumonia, and pneumothorax (p = 0.123). Besides, ENUTB costs more than $2000, while CTNUTB and VNUTB cost only about $130–230. Conclusion CTNUTB is still the main bronchoscopy method we recommended, which has low cost, simple operation, and safety no less than the others. In contrast, ENUTB provides a higher accuracy rate for small diameter nodules (less than 2 cm), which has a high use value and is worth promoting in the future.